Segregação socioespacial e criminalidade urbana envolvendo jovens na cidade de Uberlândia MG - Freitas, Oracilda Aparecida de (2008)
This research aimed to characterize the central criminality involving young people (15-24 years old) in the Uberlândia city, giving priority to social and spatial relations. It was identified the young offender profile in determined institution of promoting social and educational measures. The methodological procedures of the research covered: the survey and development of bibliographic references about theoretical concepts on social exclusion, violence with emphasis on urban crime perpetrated by young people, and public policies to prevent violence, the survey data from the COPOM on the violence indices at Uberlândia in 2006, highlighting the murders involving young people, the survey data in the Center for Health Information on deaths in 2006 by age, the survey; spatialization and analysis of some socioeconomic indicators of Uberlândia from Population Census of 2000 (IBGE); collection of reports on urban violence involving young people published in The Journal Correio de Uberlândia in months between January and December 2006; survey data in institutions for prevention of crime, such as the Superintendency of the Crime Prevention and CISAU -- Centre for Adolescent Social Integration of Uberlândia, now called Centre Social and educational of Uberlândia, and removal and analysis of some public policies for prevention of violence involving young people, formulated and implemented in other cities of the country. It was noted that in local neighbourhoods has been greater share of crimes involving young people, but it also occurs in other central districts of the city. Thus, we consider that the young is target of crime in urban social and economic context in which we live and it is for the state plan public policies aimed at education and prevention measures and combat urban violence so that it does not become author and victim of homicide reported in the media.